THE MEDIATING ROLE OF FINANCIAL MANAGEMENT IN ENHANCING MANAGERIAL PERFORMANCE IN ZAKAT MANAGEMENT INSTITUTIONS - Waldelmi, Idel; Afandi, Azhar; Fatkhurahman, Fatkhurahman; Murnawati, Murnawati (Faculty of Economic and Business, University of Pasundan, 2025)
This study aims to analyze the influence of social entrepreneurship, organizational culture, and leadership on financial managers and its impact on managerial performance. Financial management in zakat management institutions (LAZ) faces unique challenges, particularly in maintaining transparency and accountability in financial reporting, which are key demands from donors and stakeholders. This research confirms the position of financial management in improving manajerial Performance in zakat collection institutions. Employing quantitative methods, data were collected from 210 administrators of zakat institutions. Data analysis techniques using SEM. The findings indicate that financial management is influenced by social entrepreneurship, organizational culture, and leadership, which collectively impact managerial performance. This research contributes scientifically to the refinement of financial management models for social institutions and practically to more effective managerial performance.